The Effectiveness of Video-Based Audiovisual Media in Enhancing Elementary School Students’ Motivation to Elementary School Students to PPKN - Endang Pujiastuti; Herisa Hardiyanti Sholeha; Siti Ruhaya (Universitas Lambung Mangkurat, 2026)
This study aims to analyze the effectiveness of applying motion video-based audiovisual media in increasing the learning motivation of fourth-grade students in PPKN at Cibadak Public Elementary School, Sukaresmi District, Cianjur Regency. The study used a quantitative approach with a quasi-experimental pretest-posttest control group design. The research sample consisted of 60 fourth-grade students divided into two groups: the experimental group (30 students) and the control group (30 students), who received conventional learning using the lecture method. Data were collected using a learning motivation questionnaire based on a Likert scale. Instrument testing showed that all questionnaire items were valid with correlation coefficients ranging from r = 0.41–0.78. The reliability test using Cronbach’s Alpha showed a value of α = 0.89, indicating that the instrument was highly reliable. Prior to hypothesis testing, the data were analyzed using the Shapiro–Wilk normality test and Levene’s homogeneity test. The data were normally distributed and homogeneous (p > 0.05). Hypothesis testing was conducted using one-way ANOVA with a significance level of α = 0.05. The results showed a significant difference in learning motivation between the experimental and control groups (p < 0.05). Cohen's d = 4.32 (experimental) and d = 4.13 (control) indicated a significant effect of motion video media on learning motivation. The study concludes that motion-video-based audiovisual media effectively increase the motivation to learn among fourth-grade PPKN students. The practical implication of this study is the need to integrate video media into the PPKN lesson plan and provide ICT facilities in elementary schools.